Pemanfaatan Tanaman Obat Keluarga untuk Meningkatkan Kesehatan melalui Kegiatan Sosialisasi bagi Organisasi PKK di Dusun Pondok Purnawira - Komang Widhya Sedana Putra P; Ni Komang Sri Berliana Dewi; Wayan Sri Maitri (Yayasan Inspirasi El Burhani, 2025)
Introduction: Family Medicinal Plants (TOGA) serve as a natural solution for fulfilling family health needs. However, the knowledge and awareness of the PKK women regarding the benefits and cultivation of TOGA remain limited. Therefore, socialization and training are necessary to enhance their understanding and skills in utilizing TOGA effectively. Objective: This program aims to improve the knowledge and skills of PKK women in Dusun Pondok Purnawira in cultivating and utilizing TOGA as an alternative for family health maintenance and exploring its economic potential. Method: The activities were conducted through socialization and hands-on practice in the form of an interactive seminar. Participants were introduced to various types of TOGA, their benefits, and simple cultivation techniques using eco-friendly planting media. Educational materials were also shared via the PKK WhatsApp group to minimize paper waste and ensure easy access to information. Result: After the program, participants demonstrated increased knowledge about the benefits and cultivation of TOGA. They began implementing planting practices using recycled materials as planting media. Additionally, discussions emerged on utilizing TOGA not only for health purposes but also as an economic opportunity and home beautification. Conclusion: This program successfully enhanced the awareness and skills of PKK women in cultivating and utilizing TOGA. With accessible information and practical training, participants became more independent in meeting their family’s health needs while exploring the potential of TOGA as a business opportunity. The program's sustainability can be supported through follow-up training and the use of digital platforms for continuous education.